FORENSIC ODONTOLOGY: A MYRIAD OF POSSIBILITIES (Journal of Forensic Medicine & Toxicology, 2011)
Violence and serious acts of crime pose a large problem in today’s society, with the increasing rate and sophistication of crime, it’s becoming more difficult for the collection of viable and suitable evidence, equally there has been a tremendous research which has led to advancement in the forensic odontology on a global scale. Forensic sciences is a boon to tackle the present rate of crime and dentists play a major role, as the teeth are the only pivotal structures available in a totally decomposed, burned and mutilated body, as they are not affected by extreme changes in temperature and the environmental factors. The responsibility of a dentist in gathering evidence is crucial, which has to be presented in the interest of justice(1).
Keywords: Forensic dentistry; human